2006
DOI: 10.1016/j.febslet.2006.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subcellular localization of fructose 1,6‐bisphosphatase during differentiation of isolated muscle satellite cells

Abstract: Subcellular localization of FBPase, a regulatory enzyme of glyconeogenesis, was examined inside dividing and differentiating satellite cells from rat muscle. In dividing myoblasts, FBPase was located in cytosol and nuclei. When divisions ceased, FBPase became restricted to the cytosolic compartment and finally was found to associate with the Z-lines, as in adult muscle. Moreover, a 12-fold decrease was observed in the number of FBPase-positive nuclei associated with muscle fibres of adult rat, as compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Recent studies have revealed that a regulatory enzyme of gluconeogenesis—FBPase—is localized in nuclei of proliferating cells and that nuclear transport of the enzyme is regulated by extracellular stimuli (Gizak et al 2005, 2006, 2009; Mamczur et al 2010). In contrast to dividing cells, FBPase is absent in nuclei of terminally differentiated cells (Gizak et al 2006; Mamczur et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have revealed that a regulatory enzyme of gluconeogenesis—FBPase—is localized in nuclei of proliferating cells and that nuclear transport of the enzyme is regulated by extracellular stimuli (Gizak et al 2005, 2006, 2009; Mamczur et al 2010). In contrast to dividing cells, FBPase is absent in nuclei of terminally differentiated cells (Gizak et al 2006; Mamczur et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to dividing cells, FBPase is absent in nuclei of terminally differentiated cells (Gizak et al 2006; Mamczur et al 2010). These findings point to FBPase as a protein potentially involved in cell cycle regulation and/or progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier studies have revealed that FBPase localizes within the nuclei of cells that have the potential to proliferate but that are also at least partially differentiated: in some adult mammalian cardiomyocytes (Gizak and Dzugaj 2003), in mouse cardiomyocytes cell line (HL-1) stimulated with norepinephrine leading to their adult phenotype (Gizak et al 2009), and in muscle satellite cells (Gizak et al 2006). The nuclear localization of FBPase in the developing retina suggests that, also in this tissue, the cellular action of the enzyme is related in some manner to cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In some higher eukaryotes, Fbp has been found to be associated with nuclei in different types of cells (35,66). In some cases, the localization of the protein was influenced by the growth phase of the cells (35) or by changing metabolic conditions (66).…”
Section: Vol 7 2008mentioning
confidence: 99%